Isolation and characterization of ssDNA aptamers against BipD antigen of Burkholderia pseudomallei - Selvam, Kasturi; Najib, Mohamad Ahmad; Khalid, Muhammad Fazli; Yunus, Muhammad Hafiznur; A Wahab, Habibah; Harun, Azian; Zainulabid, Ummu Afeera; Mustaffa, Khairul Mohd Fadzli; Ismail, Aziah (Elsevier, 2024)
Background: Melioidosis is difficult to diagnose due to its wide range of clinical symptoms. The culture method is time-consuming and less sensitive, emphasizing the importance of rapid and accurate diagnostic tests for melioidosis. Burkholderia invasion protein D (BipD) of Burkholderia pseudomallei is a potential diagnostic biomarker. This study aimed to isolate and characterize single-stranded DNA aptamers that specifically target BipD. Methods: The recombinant BipD protein was produced, followed by isolation of BipD-specific aptamers using Systematic Evolution of Ligands by EXponential enrichment. The binding affinity and specificity of the selected aptamers were evaluated using Enzyme-Linked Oligonucleotide Assay. Results: The fifth SELEX cycle showed a notable enrichment of recombinant BipD protein-specific aptamers. Sequencing analysis identified two clusters with a total of seventeen distinct aptamers. AptBipD1, AptBipD13, and AptBipD50 were chosen based on their frequency. Among them, AptBipD1 exhibited the highest binding affinity with a K d value of 1.0 μ M for the recombinant BipD protein. Furthermore, AptBipD1 showed significant specificity for B. pseudomallei compared to other tested bacteria. Conclusion: AptBipD1 is a promising candidate for further development of reliable, affordable, and efficient point-of-care diagnostic tests for melioidosis.